Approaching opportunities in science and technology development in Vietnam - Hoang Xuan Long; Hoang Lan Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The article analyzes some basic characteristics of opportunities for S&T development including general S&T trends with objective necessity, numerous common S&T development trends that exist independently, and the limited scope of general S&T development trends,… The opportunity for S&T development is also a combination of the country's proactive, self-conscious development of S&T and the general trend of S&T development. These basic characteristics enable new assessments about the approach to S&T development chances in Vietnam over the past few years and some suggestions about the upcoming S&T development opportunities with The Fourth Industrial Revolution. Code: 22121801